Leading Through Uncertainty: How Transformational and Transactional Leadership Shape Employee Satisfaction and Performance in Lebanese NGOs - Madonna Salameh-Ayanian; Pauline Lakkis; Nada Jabbour Al Maalouf; Mohammad Makki (Administrative Sciences)
This paper examines the impact of transactional and transformational leadership on job satisfaction and employee performance during crises, focusing on the non-governmental organization (NGO) sector. The paper adopts a quantitative research methodology using an online structured questionnaire. Data from 425 NGO employees in Lebanon were analyzed using descriptive statistics, factor analysis, and structural equation modeling to test the proposed hypotheses. Transactional leadership came to have a modest positive effect on job satisfaction, aligning with previous research that highlights the importance of contingent rewards and supportive supervision. However, it did not significantly influence employee performance, suggesting that its effectiveness may be constrained by the challenges of a volatile crisis environment. In contrast, transformational leadership emerged as a key driver of both job satisfaction and employee performance, emphasizing its critical role in fostering motivation, resilience, and adaptability during turbulent periods. Notably, job satisfaction did not have a significant impact on employee performance, challenging conventional assumptions and underscoring the need for further exploration of context-specific factors in high-stress organizational settings. The findings of the paper contribute to leadership theory and provide actionable insights for enhancing NGO performance in crises.